'Neath the Arizona skies - Fraser, Harry, 1889-1974; Tuttle, Burl R., 1894-1960; Wayne, John, 1907-1979; Lone Star Productions; Cinetel Films ([Los Angeles, CA] : Lone Star Productions, 1934)
When her mother dies, a little Indian girl becomes heiress to land rich with oil. Her guardian must get her father to sign the legal papers to make the money hers. But Sam Black and the renegades aim to get to the father first, and, if necessary, kidnap the little girl.
Originally released as a motion picture in 1934.
"A Paul Malvern Production."
John Wayne, Sheila Terry, Shirley Jane Ricketts, Jack Rockwell, Yakima Canutt, Weston Edwards, Buffalo Bill, Jr., Phil Keefer.
Cinematographer, Archie Stout; editor, Charles Hunt; music, Billy Barber.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Outlaws -- Arizona -- Drama; Indians of North America -- Arizona -- Drama; Kidnapping -- Arizona -- Drama; Western films; Feature films; Internet videos; Short films; Streaming video